Effects of long-term periodized carbohydrate intake on body composition, substrate metabolism and running performance in recreational active men: A pilot trial - Anna Maria Moitzi; Andreas Feichter; Daniel König (Bern Open Publishing, 2024)
Introduction & Purpose It is important to consider the impact of nutrition on training adaptations and performance outcomes (Jeukendrup, 2017). The present study was therefore conducted with the objective of determining whether long-term periodizing carbohydrate (CHO) intake during an eight-week endurance training plan has any benefit in comparison to a traditional high-CHO or low-CHO diet in terms of running performance, substrate metabolism and body composition in recreational active males. Methods In a controlled, randomised, parallel-group and free-living design, recreationally active runners (n = 24, VO2 peak: 51 ± 8 mL·min-1·kg-1) completed 8 weeks of an ad-libitum dietary intervention (LCHF[low CHO, high fat]/CHO: 4-week regimen with ≤ 50 g CHO per day directly followed by a 4-week regimen comprising 50-60% of daily energy intake from CHO, n = 8; CHO/CHO: 8-week regimen comprising 50-60% of daily energy intake from CHO, n = 9; LCHF/LCHF: 8-week regimen with ≤ 50 g CHO per day, n = 7) together with 5 prescribed sessions of an endurance training program. Dietary recalls were conducted 3 times a week. Body composition, performance and substrate metabolism were assessed 3 times during the study (T -0, T -1 and T -2) using bioelectric impedance and a graded exercise test on a treadmill starting at 6 km·h−1 with increasing speed by 1.5 km·h−1 every 3 minutes until exhaustion. Data were analysed using a 2-way mixed ANOVA and are presented as mean ± STD. Significance was set at p < 0.05. Results Peak running speed (PRS) and time to exhaustion (TTE) demonstrated an increase over time, with no additional benefit observed in relation to any group. Total fat oxidation and maximum fat oxidation (MFO) increased in the first half of the LCHF/CHO diet and decreased during the CHO rich diet (p < 0.001). In LCHF/LCHF fat oxidation and MFO increased from T -0 to T -1 (p < 0.001) and remained unchanged at T -2. In CHO/CHO no changes in fat oxidation or MFO were observed (p > 0.05). Total fat oxidation and MFO were significantly higher at T -1 in LCHF/CHO and LCHF/LCHF compared to CHO/CHO (p < 0.05). However, at T -2 fat oxidation and MFO were significantly higher in LCHF/LCHF compared to LCHF/CHO and CHO/CHO (p < 0.05). Significant reductions in weight, BMI, and absolute fat mass were observed in LCHF/CHO from T -0 to T -1 (p < 0.05) without any further changes until T -2. For LCHF/LCHF weight and BMI were significantly reduced in the first four weeks (p < 0.001) and even further reduced in the second half (p < 0.05). For CHO/CHO no significant changes in body composition were observed (p > 0.05). Discussion & Conclusion As previously noted, a high-fat diet resulted in a greater reliance on fat oxidation during exercise (Cao et al., 2021). Here, long-term periodisation of CHO according to the preferred training adaptation leads to changes in substrate metabolism during exercise in terms of improved fat oxidation during a LCHF diet and restoration of CHO oxidation during a CHO-rich diet. Despite the observed improvements in PRS and TTE over the course of the study, no significant advantage was demonstrated by any of the groups in comparison to the other trial groups. References Cao, J., Lei, S., Wang, X., & Cheng, S. (2021). The effect of a ketogenic low-carbohydrate, high-fat diet on aerobic capacity and exercise performance in endurance athletes: A systematic review and meta-analysis. Nutrients, 13(8), Article 2896. https://doi.org/10.3390/nu13082896 Jeukendrup, A. E. (2017). Periodized nutrition for athletes. Sports Medicine, 47(S1), 51-63. https://doi.org/10.1007/s40279-017-0694-2